Analysis of Positional Differences in the Thai National Football Team Players' Performance Using Global Positioning System Tracking - Wattana Nuttouch; Poramet Hemarachatanon; Soontaraporn Huntula (OVS LLC, 2023)
Study purpose. The understanding of a performance profile in field sports using global positioning systems provides crucial data for the development of athletes in each position. In order to better understand the physiological demands placed on individual football player positions as center back, defender, midfielder, and forward during games in terms of speed, total distance covered, and number of sprints, the data were recorded using Global Positioning Systems technology. Materials and methods. From 22 official games, the professional Thai national football team players were selected. An analysis of the physiological demands placed on Thai national football team players in terms of speed, total distance traveled, number of sprints, and maximum speed measured was carried out. The analysis data were obtained through 22 matches with four player positions (center back, defender, midfielder, and forward). Results. The distance indicator in the individual position of a forward player was significantly higher when compared to a defender (p = 0.0006). At the high-intensity running zone, the distance covered by a forward was found to be significantly higher when compared to any other zone. Furthermore, the sprint and maximum speed indicators in the forward position of a professional Thai national football player were shown higher than in the center back, defender and midfielder positions (p = 0.0001, p = 0.0001 and p = 0.0046, respectively). Conclusions. The Thai national football team players' performance per complete game in this study was lower than that of foreign professional teams in terms of their total distance and high-intensity running. With the use of a greater quantity of data and more accurate calculation techniques, coaches and training staff will be able to develop appropriate routines to enhance the competition preparation level of the professional Thai national football team players.